The Influence Of The Internet On Business: The Need To Adapt To Changes In The Digital Era - Nurul Fadila; Muhammad Rizqi; siti aisyah; serli Anjeli Robbi (International Journal of Management and Business Economics, 2026)
This study examines the impact of internet technology on business development within the context of digital transformation. The rapid advancement of internet-based technologies has fundamentally reshaped business structures, shifting traditional linear value chains toward integrated digital ecosystems. This study aims to synthesize how internet utilization influences business model innovation, marketing transformation, strategic adaptation, human resource development, and cybersecurity management. The study employs a conceptual synthesis approach based on existing literature on digital transformation, platform economy, dynamic capabilities, and organizational change. The findings indicate that internet technology serves as a foundational infrastructure that enables the emergence of platform-based business models, enhances global market accessibility, and supports data-driven decision-making processes. In addition, digital marketing has evolved into an interactive and customer-centered system, driven by big data analytics, social media engagement, and omnichannel communication strategies. Furthermore, the analysis reveals that human resource capabilities play a critical role in determining the success of digital transformation initiatives. Organizations require continuous workforce reskilling, digital literacy enhancement, and adaptive leadership to effectively respond to technological disruption. The study also identifies cybersecurity as a major challenge in digital business environments, requiring integrated governance, technical safeguards, and organizational awareness to mitigate risks related to data breaches and cyber threats. Based on the synthesis of findings, this study proposes a conceptual framework consisting of five interconnected dimensions: technological adoption, business model innovation, strategic adaptation, human resource development, and cybersecurity management. The interaction among these dimensions determines the effectiveness of internet-driven business transformation. The study concludes that sustainable competitive advantage in the digital era depends on the ability of organizations to integrate technological capabilities with managerial strategies and human capital development within dynamic digital ecosystems.